Commercio e governo della città in età fascista. Per uno studio di storia urbana - Roberto Parisini (Storia e Futuro, 2022)
My aim is to analyze Bolognina, the biggest working-class district in Bologna, to deal with retail trade as government tool of private consumption and petty bourgeois integration of urban suburbs in cities organized by Fascism.